Magnetic endoscope imaging for routine colonoscopy: impact on propofol dosage and patient safety – a randomized trial - Klare, Peter; Hartrampf, Bonnie; Haller, Bernhard; Schlag, Christoph; Geisler, Fabian; Abdelhafez, Mohamed; Einwächter, Henrik; Bajbouj, Monther; Schmid, Roland M.; von Delius, Stefan (Endoscopy, 2016)
Background and study aim: The use of magnetic endoscope imaging (MEI) has been previously shown to facilitate colonoscopy procedures. We aimed to evaluate the benefits of MEI in terms of reduction in propofol dosage in patients undergoing routine colonoscopy.Methods: We conducted a randomized prospective trial in a university hospital in Germany. Endoscopists were randomly assigned 1:1 to use MEI during colonoscopy (MEI arm) or to conduct colonoscopy without the use of MEI (standard arm). The desired level of sedation was conscious sedation as assessed using the Observer’s Assessment of Alertness and Sedation scores. After complete recovery, patient satisfaction was assessed using a numeric rating scale (NRS) ranging from 1 to 10 points. The primary outcome was total propofol dosage. Secondary outcome measures were patient satisfaction, patients’ cooperation, and complication rates, as well as cecal intubation time and adenoma detection. Results: Among 334 randomized patients, no severe adverse events were observed. Median propofol dosage was significantly lower in the MEI arm compared with the standard arm (150 mg vs. 180 mg; P = 0.04). Deep sedation was observed in 7.8 % of patients in the MEI group and 3.6 % in the standard arm (P = 0.10). Patient satisfaction scores were higher in the MEI arm compared with standard procedures (9.0 vs. 8.5; P = 0.04). No significant differences in patients’ cooperation, cecal intubation time, and adenoma detection were observed between the study arms.Conclusion: The use of MEI may be useful in reducing propofol dosage for colonoscopy and improving patient satisfaction.ClinicalTrials.gov identifier: NCT02121704.